Can Pedagogical Innovations Be Sustainable? One Evaluation Outlook for Research Developed in Portuguese Higher Education - Cecília Guerra; Nilza Costa (Education Sciences, 2021)
Across higher education, teachers have been inspiring themselves (and others) to apply pedagogical innovations grounded in a unifying intention: to prepare students for labour markets and societal challenges. Research-based education has been funded to promote pedagogical innovations with valuable impact on the students’ academic success and/or the teachers’ academic growth. However, there is still few documented research-based evidence that highlight how long-lasting and/or how embedded are the pedagogical innovations in academic practices, particularly when the funding period comes to an end. The purpose of this article is to discuss the extent to which funded national research-based education projects, developed in public Portuguese higher education institutions (universities and polytechnic institutes), have considered the sustainability of research results (e.g., pedagogical innovations), after funding ends. Based on a qualitative research approach, data collection included: document analysis of 39 projects’ materials and conceptions collected with 9 coordinators and 17 key participants from selected projects, through interviews and questionnaires, respectively. Content analysis of data collected showed that there are key factors that contribute to enhance and/or limit the sustainability of research results (e.g., funding and institutional support to maintain innovation). Results and recommendations are put forward to inform educational policies, funding agencies and involved actors (e.g., institution leaders, researchers, and teaching staff) to increase the sustainability of research results.